Мультимедія як модернізаційний напрямок навчання в процесі викладання курсу «Історія України» - Телуха, Світлана Степанівна (НТУ "ХПІ", 2018)
Використання мультимедійних презентацій в системі сучасної освіти займає все більше місце та стає певною повсякденністю. Мультимедія під час викладання дисципліни "Історія України" є важливим елементом освітнього процесу, яка покликана мотивувати студентів до навчання, поліпшити сприйняття інформації, зробити навчальний процес сучасним, цікавим та продуктивним. Мультимедійні презентації створені викладачами та студентами постійно вдосконалюються та являються модернізаційним напрямком навчання та комунікації.

The use of multimedia presentations in the system of modern education takes up an increasing number of places and becomes a "daily routine". Multimedia during the teaching of the discipline "History of Ukraine" is an important element of the educational process. During lectures and seminars, using the multimedia technologies is a topical issue today. Multimedia is designed to motivate students to study, improve perceptions of information, make the learning process interesting and productive. Multimedia presentations created by lecturers and students serve as a kind of communication. They are constantly improving and being a modernization training area.
Multimedia as a modernization direction in the course of teaching "History of Ukraine"
Keywords: інформаційні технології; презентація; освіта; освітній процес; information technologies; presentation; education